The Visualization of the Impact of Covid-19 On Education Field: A Bibliometric Study - Laela Sagita; Rully Charitas Indra Prahmana (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
The COVID-19 pandemic has made researchers from various fields make fundamental contributions according to their expertise. One of which is in the education field. The field has created research results and published them in reputable journals to increase the readability for the community. The published researches provide an overview of the challenges of teaching and learning activities during the pandemic and the solutions offered. This study presents the analysis results using the Bibliometrix R-Package on 950 data sourced from the Scopus database during the years 1990-2022. The analysis and visualization results show contributors at various levels, including authors, institutions, and countries, as opportunities to open collaboration between researchers and institutions. In addition, the study also identified several keywords that can be used as an essential point to determine the novelty or direction of future research. Finally, this study contributes as a roadmap to potential research opportunities and significant implications for future education practitioners, policymakers, and researchers in the field.